Sistem Telemetri Cerdas untuk Monitoring Kadar Particulate Matter (PM10) Menggunakan Algoritma Rule-Based Berbasis Internet of Things - Salwa, Septi Lailatis; Shodiq, Muhammad; Handoyo, Eko (Journal of Computer System and Informatics (JoSYC), 2024)
Air pollution by Particulate Matter (PM10) is a pressing environmental issue that has a major impact on public health. PM10 consists of particles with a diameter of less than 10 μm that can penetrate the respiratory tract, causing respiratory infections, heart disease, and lung disorders. The main sources of this pollution include vehicle emissions, industrial activities, and organic matter burning, which often exceed the thresholds set by health agencies. This research aims to develop an Internet of Things (IoT)-based intelligent telemetry system to monitor PM10 levels in real-time using Rule-Based Algorithm sensors. This algorithm adopts artificial intelligence techniques to solve problems based on a set of predefined rules. This process involves several important stages of knowledge base collection. IoT as a low-cost device enables extensive data collection, interaction with other IoT devices, and utilization of cloud-based services and storage. This system is expected to provide accurate and fast information about the level of air pollution and increase public awareness about the importance of maintaining air quality. The results showed that the measured PM10 level in Table 1 reached 2.48 µg/m³, while in Table 2 it was 1.768 µg/m³. Both values are categorized as dangerous. The system is also equipped with a notification feature via Telegram, allowing users to monitor air quality conditions effectively. This research contributes to the development of air quality monitoring technology and environmental health.